STRATEGI PENGELOLAAN DAN PEMANFAATAN SAWAH WAKAF DI DESA KARANGJONGKENG KECAMATAN TONJONG KABUPATEN BREBES ( STUDI KASUS YAYASAN NURUDDIN KARANGJONGKENG ) - Ali Ghiyatsi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Management strategies and utilization of waqf rice field management results are the big themes that will be presented in this research. The Nuruddin Karangjongkeng Foundation is one of the foundations that has the largest waqf rice field assets in Brebes Regency. Waqf Rice Fields are productive waqf assets which, if managed properly and correctly, can achieve one of the goals of waqf, namely the welfare of the people. However, achieving the level of welfare of the people is not easy, because the role of the Nazir is very large. Nazir competence is very much needed in delivering the waqf to achieve the ideals or goals of the waqf. In other words, the Nazir has full responsibility for managing and utilizing existing waqf assets.The aim of this research is to find out the management strategy and utilization of the results of managing waqf rice fields at the Nuruddin Karangjongkeng Foundation. To answer the problem formulation in this research, the type of research used is field research (qualitative research). The methods used in collecting data are observation, interviews and documentation. This research uses data reduction techniques, data presentation, and drawing conclusions as data analysis techniquesAfter conducting research, it can be concluded that the management strategy carried out by the Nazirs of the Nuruddin Karangjongkeng Foundation is to make every Nazir at the Nuruddin Karangjongkeng Foundation the person responsible for managing the waqf rice fields, collaborating with the local community in cultivating the waqf rice fields with a profit sharing system of 1/3 for the waqf and 2 /3 for cultivators, making farmer cards to obtain more affordable fertilizer, and applying a profit sharing of ¼ part of the waqf ¾ part of the cultivator for rain-fed rice fields. The utilization strategy implemented by the Nuruddin Karangjongkeng Foundation is to utilize the results of management according to the intended use of the waqf assets and take 15% of the proceeds as maintenance funds for the waqf assets.